The Neuropeptide 26RFa (QRFP) and Its Role in the Regulation of Energy Homeostasis: A Mini-Review - Chartrel, Nicolas; Picot, Marie; El Medhi, Mouna; Arabo, Arnaud; Berrahmoune, Hind; Alexandre, David; Maucotel, Julie; Anouar, Youssef; Prévost, Gaëtan (Frontiers in Neuroscience, 2016)
This mini-review deals with the neuropeptide 26RFa (or QRFP) which is a member of the RFamide peptide family discovered simultaneously by three groups in 2003. 26RFa (or its N-extended form 43RFa) was subsequently shown to be the endogenous ligand of the human orphan receptor GPR103. In the brain, 26RFa and GPR103mRNA are primarily expressed in hypothalamic nuclei involved in the control of feeding behavior, and at the periphery, the neuropeptide and its receptor are present in abundance in the gut and the pancreatic islets, suggesting that 26RFa is involved in the regulation of energy metabolism. Indeed, 26RFa stimulates food intake when injected centrally, and its orexigenic effect is even more pronounced in obese animals. The expression of 26RFa is up-regulated in the hypothalamus of obese animals, supporting that the 26RFa/GPR103 system may play a role in the development and/or maintenance of the obese status. Recent data indicate that 26RFa is also involved in the regulation of glucose homeostasis. 26RFa reduces glucose-induced hyperglycemia, increases insulin sensitivity and insulinemia. Furthermore, an oral ingestion of glucose strongly stimulates 26RFa release by the gut, indicating that 26RFa is a novel incretin. Finally, 26RFa is able to prevent pancreatic β cell death and apoptosis. This brief overview reveals that 26RFa is a key neuropeptide in the regulation of energy metabolism. Further fields of research are suggested including the pathophysiological implication of the 26RFa/GPR103 system.